An Immune-Related Signature Predicted Survival in Patients With Kidney Papillary Cell Carcinoma - Shen, Junwen; Wang, Rongjiang; Chen, Yu; Fang, Zhihai; Tang, Jianer; Yao, Jianxiang; Ling, Yuhang; Zhang, Lisha; Zhang, Xu (Frontiers in Oncology, 2021)
Immune-related genes are important factors in tumor progression. The main aim of this study was to identify the immune-related genes in Kidney papillary cell carcinoma (pRCC) patients. We downloaded RNAseq data and clinical information of pRCC patients from the TCGA database and retrieved the immune-related genes list from Immport. From the data, we mined out 2468 differential expression genes (DEGs) and 183 immune-related DEGs. Four hub DEGs (NTS, BIRC5, ELN, and CHGA) were identified after conducting Cox analysis and LASSO analysis. Moreover, the prognostic value of the signature based on 4 hub DEGs was verified using Kaplan-Meier analysis (P=0.0041 in the training set and p=0.021 in the test set) and ROC analysis (AUC: 0.957 in 1 year, 0.965 in 2 years, and 0.901 in 3 years in the training set, and 0.963 in 1 year, 0.898 in 2 years, and 0.742 in 3 years in the test set). Furthermore, we found that the high-risk score group had a higher percentage of B cells in the immune component, a higher expression of immune-related genes (CTLA4, LAG3, PDCD1LG2, and TIGIT), and a better immunotherapy response.